Preparation method of bio-based composite polylactic acid fiber

Through alkaline solvent pretreatment and polyisocyanate compound treatment, the interface compatibility between plant fibers and polylactic acid is improved, and the problem of poor interface compatibility between plant fibers and polylactic acid is solved, which is significantly improved the physical and mechanical properties of the composite material.

CN119553387AInactive Publication Date: 2025-03-04JIANGSU RUNZHAO NEW MATERIALS TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411850355.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The interface compatibility between plant fibers and polylactic acid is poor, affecting the physical and mechanical properties of composite polylactic acid fiber materials.

Method used

The gum on the surface of the plant fibers was removed by alkaline solvent pretreatment, exposing the hydroxyl functional groups on the surface of the cellulose, and the plant fibers were treated with organic polyisocyanate compounds, so that the surface of the plant fibers changed from hydrophilic to lipophilic, thereby improving interface compatibility.

Benefits of technology

The interface compatibility between plant fibers and polylactic acid is significantly improved, and the physical and mechanical properties of composite materials are enhanced, including the improvement of tensile strength and impact strength.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a preparation method of bio-based composite polylactic acid fibers, and relates to the field of biomass conversion materials and composite polylactic acid fibers.The flexible hydrogen conveying pipe is prepared from polylactic acid, polyester fibers, graphene fibers, natural plant fibers, jasmine extract, carbodiimide, triacetic acid and acetyl tributyl citrate. The natural plant fibers comprise linen fibers, natural corn fibers and wormwood fibers which are microfibers; according to the preparation method disclosed by the invention, the interface compatibility of the natural plant fibers and the polylactic acid is improved after the natural plant fibers are integrally modified, the physical and mechanical properties of the finally prepared bio-based composite polylactic acid fiber material are enhanced, and various properties of the prepared bio-based composite polylactic acid fiber material are in higher standards in the composite polylactic acid fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of biomass conversion materials and composite polylactic acid fiber manufacturing, and specifically provides a method for preparing bio-based composite polylactic acid fiber. Background Art

[0002] Polylactic acid fiber (PLA fiber) is a synthetic fiber that is easy to grow and can be naturally degraded in nature. It is made from starch-containing agricultural products such as corn and wheat, and is fermented to produce lactic acid, which is then polycondensed and melt-spun. It has the advantages of good biocompatibility, antibacterial properties, flame retardancy and full biodegradability. Its fabric is soft to the touch and has good drape. It is suitable for various fashions, casual wear, sports goods and sanitary products, etc., and has broad application prospects.

[0003] Plant fiber reinforced polylactic acid composite materials use natural plant fibers, pure cellulose or its derivatives as bio-based modifiers or reinforcing materials, and combine with polylactic acid to create high-performance biomass composite materials. Polylactic acid comes from renewable resources and is both biodegradable and biocompatible; while natural plant fibers are low-cost, renewable, easily degradable, and have the advantages of low density and high strength. With the improvement of ecological and environmental awareness, this composite material has become a hot focus in the field of "green composite materials".

[0004] In the research of plant fiber reinforced thermoplastic composites, the biggest problem is that the cellulose surface in the plant fiber contains a large number of strongly polarized hydroxyl groups, which makes the plant fiber polar and hydrophilic. This property greatly affects the interfacial compatibility between the plant fiber and the polylactic acid matrix, resulting in poor adhesion between the plant fiber and the polylactic acid matrix, which seriously affects the physical and mechanical properties of the composite polylactic acid fiber material. Summary of the invention

[0005] In view of the defects existing in the above-mentioned prior art, the present invention provides a method for preparing bio-based composite polylactic acid fiber, which solves the problem of improving the interface compatibility between plant fiber and polylactic acid, and improving the physical and mechanical properties of composite polylactic acid fiber to reach higher standards.

[0006] The objective of the present invention is achieved through the following technical scheme. The raw material components of the flexible hydrogen transmission pipe include polylactic acid, polyester fiber, graphene fiber, natural plant fiber, jasmine extract, carbodiimide, triacetic acid, acetyl tributyl citrate, and the natural plant fiber includes flax fiber, natural corn fiber, and wormwood fiber, all of which are microfibers; the preparation method includes the following steps:

[0007] S1: First, the colloid on the surface of the natural plant fiber is removed by pretreatment with an alkaline solvent to expose the functional groups of the hydroxyl groups on the surface of the cellulose, and then the natural plant fiber is treated by dissolving the polyisocyanate compound in an alcohol solution;

[0008] S2: Under anhydrous conditions, corn fiber and acetoacetic acid are mixed in proportion, and hydroxyl groups on the surface of the corn fiber are modified by acetoacetic acid to obtain modified corn fiber A;

[0009] S3: Laccase was used to degrade the lignin and cellulose network structure in flax fiber and wormwood fiber to disperse the fiber bundles, succinic anhydride was used to esterify the wormwood fiber to improve the interfacial compatibility between the fiber and the polymer matrix, and the esterified wormwood fiber was immersed in a lithium silicate mixed solution for coating to improve the thermal stability of the plant fiber, thereby obtaining modified wormwood fiber A;

[0010] S4: soaking the degraded flax fiber in an acetylation agent solution, adding a trace amount of Lewis acid as a catalyst, acetylation treatment of the flax fiber, enhancing the interfacial bonding force between the flax fiber and the polymer matrix, and obtaining acetylated flax fiber. After the acetylation treatment is completed, a weak base (such as sodium carbonate solution) is used to neutralize the residual acid to prevent further degradation of the fiber, and the acetylated flax fiber is washed with a large amount of water to remove unreacted acetylation agent, catalyst and by-products, and the washed acetylated flax fiber is dried at low temperature to prevent heat damage, thereby obtaining modified flax fiber A.

[0011] S5: Using hot volatile gas of hexamethyldisiloxane as the gas medium, a low-temperature plasma treatment apparatus was used to post-treat the three treated natural plant fibers at normal pressure to obtain modified flax fiber B, modified corn fiber B, and modified wormwood fiber B, thereby improving the interface compatibility between the fiber and the polymer matrix and enhancing the performance of the composite material;

[0012] S6: dissolving jasmine extract in a solvent, stirring the solvent sufficiently to ensure that the extract is completely dissolved, immersing polyester fiber in the solution containing jasmine extract, mechanically stirring the solution so that the jasmine extract is loaded on the polyester fiber, taking out the fiber and drying it at 35° C., and performing heat setting treatment on the dried fiber to enhance the persistence of the fragrance, thereby obtaining loaded polyester fiber A;

[0013] S7: polylactic acid is dried at high temperature, and the dried polylactic acid, graphene fiber and carbodiimide are first added to a mixing device for plasticizing and blending for 3 hours, with the temperature set at 165°C and the speed set at 50r / min. After the initial blending, triacetic acid, modified flax fiber B, modified corn fiber B, modified wormwood fiber B and acetyl tributyl citrate are added, and plasticizing and blending are performed for 5 minutes. Then, the loaded polyester fiber A is added and plasticized and blended again for 20 minutes, with the temperature set at 160°C and the speed set at 50r / min. After plasticizing and melting evenly, sheets are produced, and after lamination, they are hot pressed on a flat vulcanizer while hot, and then cold pressed on a cold press to room temperature, and dried and formed to obtain standard specimens;

[0014] S8: irradiating the standard sample with gamma rays to obtain the final product, i.e., bio-based composite polylactic acid fiber.

[0015] In the above-mentioned method for preparing bio-based composite polylactic acid fiber, preferably, in the step S1, the alkaline solvent used for pretreatment is NaOH solution; the concentration of the NaOH solution is 3-5%; the pretreatment temperature is 30-58°C;

[0016] As the most preferred, a 3% concentration of NaOH solution is selected as the pretreatment solvent, and the pretreatment temperature is 55° C. A temperature exceeding 60° C. will increase the risk of fiber damage, and a higher temperature can effectively remove lignin in natural plant fibers.

[0017] In the above-mentioned method for preparing bio-based composite polylactic acid fiber, preferably, in the step S1, the polyisocyanate compound is selected from one of polyphenyl polyisocyanate, cyanurate, toluene diisocyanate and diphenylmethane diisocyanate; the alcohol solution is selected from one of propanol, pentanol, dodecanol and dodecanol mercaptan;

[0018] As the most preferred embodiment, the polyisocyanate compound is polyphenyl polyisocyanate, and the alcohol solution is propanol. The surface of the natural plant fiber is changed from hydrophilic to lipophilic by treatment with the polyisocyanate compound, thereby improving the interfacial compatibility between the plant fiber and the polymer matrix.

[0019] In the above-mentioned method for preparing bio-based composite polylactic acid fiber, preferably, in the step S2, before mixing the corn fiber with acetoacetic acid, one of anhydrous sodium sulfate and molecular sieve is used to remove moisture; the reaction temperature is reflux temperature; the feed mass ratio of corn fiber to acetoacetic acid is 1:1.5-2;

[0020] As the most preferred option, the mass ratio of corn fiber to acetoacetic acid is 1:1.5. There are a large number of hydroxyl groups on the surface of corn fiber, which is extremely hydrophilic. The hydroxyl groups on the surface of corn fiber can provide a large number of active reaction sites. After the acetylation reaction, the hydroxyl groups can be greatly reduced, thereby reducing water absorption.

[0021] In the above-mentioned method for preparing bio-based composite polylactic acid fiber, preferably, in the step S3, the lithium silicate mixed solution is prepared by mixing lithium silicate powder with ethanol solution, and the lithium silicate powder accounts for 5-10% of the total mass of the solution;

[0022] As the most preferred choice, lithium silicate coating can effectively improve the thermal stability of mugwort fiber, enabling it to withstand higher temperature environments and increase its application range.

[0023] In the above-mentioned method for preparing bio-based composite polylactic acid fiber, preferably, in the step S4, the acetylation agent is selected from acetyl chloride and acetic anhydride; the reaction temperature is 40-80°C; the low-temperature drying temperature is 0-10°C;

[0024] As the most preferred, the acetylation agent is acetyl chloride, the reaction temperature is 60°C, and the low-temperature drying temperature is 5°C. The acetylation modification enhances the interfacial bonding force between the flax fiber and the polymer matrix.

[0025] In the above-mentioned method for preparing bio-based composite polylactic acid fiber, preferably, in the step S6, the mass ratio of polyester fiber to jasmine extract is 1:0.025-0.05; the solvent is selected from ethanol and acetone;

[0026] As the most preferred, the mass ratio of polyester fiber to jasmine extract is 1:0.04. After the polyester fiber is loaded with jasmine extract, the adsorption capacity of aroma components is enhanced, which can play a partial protective role in the smelting process.

[0027] In the above-mentioned method for preparing bio-based composite polylactic acid fiber, preferably, in the step S7, the components and addition amounts of the main raw materials are: 60 parts of polylactic acid, 3 to 7 parts of graphene fiber, 12 to 18 parts of modified flax fiber B, 4 to 10 parts of modified corn fiber B, 2 to 4 parts of modified wormwood fiber B, and 8 to 12 parts of loaded polyester fiber A;

[0028] As the most preferred option, the components and addition amounts of the main raw materials are: 60 parts of polylactic acid, 5 parts of graphene fiber, 15 parts of modified flax fiber B, 7 parts of modified corn fiber B, 3 parts of modified mugwort fiber B, and 10 parts of loaded polyester fiber A. When the content of natural plant fiber is close to 30%, the tensile strength and impact strength of the finished bio-based composite polylactic acid fiber reach a higher level.

[0029] In the above-mentioned method for preparing bio-based composite polylactic acid fiber, preferably, in the step S7, the amount of anti-aging agent carbodiimide added is 1-3% of the amount of the main raw material added; the amount of acetyl tributyl citrate added is 0.5-1.1% of the amount of the main raw material added;

[0030] As the most preferred, carbodiimide can effectively inhibit the hydrolysis process of ester bonds in the molecular chain of polylactic acid fibers and reduce the biodegradation rate of the composite material. Adding a small amount of acetyl tributyl citrate is beneficial to improving the compatibility of natural plant fibers and polylactic acid composite systems.

[0031] In the above-mentioned method for preparing bio-based composite polylactic acid fiber, preferably, in the step S8, the radiation sensitizer is triallyl isocyanuric acid, and the amount of the radiation sensitizer added is 2%; the radiation dose is 30 kGy;

[0032] As the most preferred embodiment, when the γ-ray radiation dose is 30 kGy, the tensile strength and flexural strength of the modified bio-based composite polylactic acid fiber are both moderately improved.

[0033] In summary, compared with the prior art, the present invention has the following advantages:

[0034] 1. In the scheme of the present invention, the colloid on the surface of the plant fiber is removed by pretreatment with an alkaline solution to expose the hydroxyl functional groups on the surface of the natural plant fiber, and then the plant fiber is treated with an organic polyisocyanate compound. The surface of the natural plant fiber is changed from hydrophilic to lipophilic by the polyisocyanate compound treatment, thereby improving the interfacial compatibility between the plant fiber and the polymer matrix;

[0035] 2. In the scheme of the present invention, there are a large number of hydroxyl groups on the surface of natural corn fiber, which is extremely hydrophilic. The hydroxyl groups on the surface of corn fiber can provide a large number of active reaction sites. After the acetylation reaction, the hydroxyl groups can be greatly reduced, thereby reducing the water absorption;

[0036] 3. In the scheme of the present invention, laccase is used to degrade the lignin and cellulose network structure in the natural plant fiber, so that the fiber bundles in the natural plant fiber are dispersed, and then the fiber bundles are subjected to an esterification reaction, thereby greatly improving the water resistance of the wormwood fiber and improving the interfacial compatibility between the wormwood fiber and polylactic acid. The lithium silicate mixed solution can form a film on the surface of the plant fiber, thereby improving the thermal stability of the plant fiber.

[0037] 4. In the scheme of the present invention, the interfacial bonding force between the flax fiber and the polymer matrix is ​​enhanced by acetylation modification. After the flax fiber is modified, the melting temperature of the composite material is relatively stable, and the tensile strength of the composite material is enhanced to a certain extent. According to the test, the tensile strength of the composite material is increased by more than 12% compared with that of the untreated flax fiber / polylactic acid fiber.

[0038] 5. In the scheme of the present invention, a non-polar carbon-silicon compound coating is deposited on the surface of the natural plant fiber after being treated with the hot volatile gas of hexamethyldisiloxane, which can enhance the interfacial compatibility between the natural plant fiber and polylactic acid and enhance the mechanical properties of the composite material to a certain extent;

[0039] 6. In the scheme of the present invention, after the polyester fiber is loaded with jasmine extract, the adsorption capacity of the aroma components is enhanced, which can play a partial protective role in the smelting process to enhance the persistence of the aroma. After the smelting is completed, a sealing effect will also be produced to further lock the aroma and prevent the aroma from volatilizing quickly;

[0040] 7. In the scheme of the present invention, carbodiimide can effectively inhibit the hydrolysis process of the ester bond in the molecular chain of polylactic acid fiber, reduce the biodegradation rate of the composite material, and a small amount of acetyl tributyl citrate is beneficial to improve the compatibility of the natural plant fiber and polylactic acid composite system;

[0041] 8. In the scheme of the present invention, the sample strips of the bio-based composite polylactic acid fiber are modified after being irradiated with gamma rays, and the tensile strength and bending strength of the modified bio-based composite polylactic acid fiber are moderately improved. DETAILED DESCRIPTION

[0042] In order to explain the technical content, structural features, achieved objectives and effects of the present invention in detail, further description is given below in conjunction with specific embodiments.

[0043] Embodiment 1:

[0044] Flax fiber, natural corn fiber and wormwood fiber are placed in a 3% NaOH solution (the mass ratio of natural plant fiber to NaOH solution is 1:50), the temperature is raised to 55°C, the ultrasonic frequency is 300Hz for reaction for 1h, and after alkali treatment, they are washed with water to neutrality, and the temperature is set to 60°C for drying for 25min; polyphenyl polyisocyanate is dissolved in propanol and diluted to a 10% solution, the alkali-treated natural plant fiber raw material is slowly added, the material is stirred at room temperature for 20 to 40min, and the pretreated natural plant fiber raw material is obtained after drying at 55°C.

[0045] The natural corn fiber was dehydrated by using anhydrous sodium sulfate or molecular sieves, added into isopropanol, the temperature was raised to 73°C and stirred continuously, 1.5 times the mass of corn fiber tert-butyl acetoacetate was slowly added dropwise, and the reaction was carried out for 20 to 40 minutes. After the reaction was completed, the temperature was lowered to room temperature, allowed to stand for stratification, and then filtered. The filter cake was washed with anhydrous ethanol and dried at 45°C to obtain modified corn fiber A.

[0046] The flax fiber and wormwood fiber raw materials are placed in a container containing an acetic acid-sodium acetate buffer solution with a volume concentration of 4.8%, laccase with a mass percentage of 3.5% of the fiber raw material is added, and the mixture is heated to 68° C. for hydrolysis reaction for 4 hours. After filtering out the reactants, the mixture is rinsed to neutrality and dried to obtain a fiber hydrolyzate.

[0047] A mixed solution of succinic anhydride and xylene was prepared in a mass ratio of 1:4, and then the hydrolyzate of wormwood fiber was added, and the mixture was heated at 80°C for 6 hours for esterification reaction to obtain a wet reaction product. Succinic anhydride was extracted and xylene was evaporated, and the product was spread into a 4 mm thick fiber layer and dried at 40°C to obtain an esterified wormwood fiber product.

[0048] Lithium silicate and ethanol were prepared into a mixed solution in a ratio of 1:9, and a magnesium chloride solution of 4.5% of the mass of the mixed solution was added to prepare a coating liquid. The coating liquid was evenly sprayed on the esterified wormwood fiber product at a spraying amount of 62 mL per square meter, and the product was allowed to stand at room temperature for 1 hour, dried and sieved to obtain modified wormwood fiber A.

[0049] The degraded flax fiber was placed in acetyl chloride, a trace amount of Lewis acid was added as a catalyst, and it was soaked at room temperature for 150 minutes. Sodium carbonate solution was used to neutralize it, and it was taken out and filtered. The filter cake was washed with a large amount of clean water, and it was placed in an oven at 60°C for reaction for 20 minutes. After taking out, it was dried at 5°C to obtain modified flax fiber A.

[0050] Pour hexamethyldisiloxane into a container, and connect it to a low-temperature plasma device using a valve, a flowmeter, and a high-temperature resistant hose. Heat the container containing hexamethyldisiloxane to 100° C. Place modified flax fiber A, modified corn fiber A, and modified wormwood fiber A in batches separately on a loading table in a reaction chamber of the low-temperature plasma device. Turn on the vacuum pump to evacuate the air in the reaction chamber. At the same time, fill gaseous hexamethyldisiloxane into the reaction chamber. Control the flow rate of gaseous hexamethyldisiloxane by a flowmeter. After a period of time, dynamic equilibrium is reached. Maintain one atmospheric pressure in the reaction chamber. Turn on the radio frequency power source and adjust the radio frequency power to 30 W. Perform plasma treatment on the natural plant fiber for 4 minutes. After taking out, modified flax fiber B, modified corn fiber B, and modified wormwood fiber B are obtained.

[0051] The jasmine extract was dissolved in ethanol solvent in proportion, a trace amount of polyethylene glycol was added as a dispersant, the polyester fiber was immersed in the jasmine extract solution and kept for 3 hours, the fiber was taken out in the middle and the excess solution was removed by squeezing the fiber, and the reaction was repeated for many times. After the reaction was completed, the product was taken out and the fiber was allowed to dry naturally at room temperature, and the fiber was thoroughly dried in an oven at a temperature of 35°C to fix the jasmine extract on the fiber, and the product was put into the oven again and heated to 60°C and then isothermally annealed to obtain loaded polyester fiber A.

[0052] Embodiment 2:

[0053] Weigh 60 parts of polylactic acid, 5 parts of graphene fiber, 15 parts of modified flax fiber B, 7 parts of modified corn fiber B, 3 parts of modified wormwood fiber B, and 10 parts of loaded polyester fiber A;

[0054] The polylactic acid is dried at high temperature, and the dried polylactic acid, graphene fiber and carbodiimide are first added to a mixing equipment for plastication and blending for 3 hours, with a set temperature of 165°C and a rotation speed of 50r / min. After the initial blending is completed, triacetic acid, modified flax fiber B, modified corn fiber B, modified wormwood fiber B and acetyl citrate tributyl ester are added, and plastication and blending are performed for 5 minutes. Then, the loaded polyester fiber A is added and plastication and blending are performed again for 20 minutes, with a set temperature of 160°C and a rotation speed of 50r / min. After plastication and melting are uniform, sheets are produced, and after lamination, they are hot-pressed on a flat vulcanizer while hot, and then cold-pressed on a cold press to room temperature, dried and formed to obtain a standard specimen, and the standard specimen is irradiated with gamma rays. The radiation sensitizer is triallyl isocyanuric acid, and the amount of the radiation sensitizer added is 2%; the radiation dose is 30kGy, and the final product, i.e., bio-based composite polylactic acid fiber, is obtained.

[0055] Embodiment 3:

[0056] The bio-based composite polylactic acid fiber was clamped on a universal testing machine, the tensile speed was set to 2 mm / min, and the test was carried out according to GB / T 1040.3-2006 standard. The test was repeated five times, and the average values ​​were taken as the elongation at break and tensile strength of the sample.

[0057] The bio-based composite polylactic acid fiber was clamped on a universal testing machine with a span of 60 mm. The bending speed was set to 2 mm / min and the test was carried out according to GB / T 9341-2008 standard. The test was repeated five times and the average value was taken to obtain the bending strength.

[0058] The bio-based composite polylactic acid fiber was clamped on a J-type pendulum impact testing machine without making a notch, and tested according to GB / T1843-2008 standard for five times, and the average value was taken as the impact strength.

[0059] Polylactic acid fibers were purchased from the market and tested one by one according to the above test conditions. The comparison results are shown in the following table:

[0060] Tensile strength(MPa) Elongation at break (%) Bending strength(MPa) <![CDATA[Impact strength (KJ / M 2 )]]> Example 2 83 656 143 6.4 Commercially available 61 547 102 3.2

[0061] It can be seen from the above table that the bio-based composite polylactic acid fiber material obtained in the embodiments of the present invention has good mechanical properties, and all performances are better than those of commercially available products.

[0062] The implementation of the present invention is not limited to the above-mentioned embodiments. Without departing from the spirit and scope of the present invention, ordinary technicians in this field can make various changes and improvements to the present invention in form and detail, and these are considered to fall within the protection scope of the present invention.

Claims

1. A method for preparing a bio-based composite polylactic acid fiber, characterized in that: The raw material components of the flexible hydrogen transmission pipe include polylactic acid, polyester fiber, graphene fiber, natural plant fiber, jasmine extract, carbodiimide, triacetic acid, acetyl tributyl citrate, and the natural plant fiber includes flax fiber, natural corn fiber, and wormwood fiber, all of which are microfibers; the preparation method includes the following steps: S1: First, the colloid on the surface of the natural plant fiber is removed by pretreatment with an alkaline solvent to expose the functional groups of the hydroxyl groups on the surface of the cellulose, and then the natural plant fiber is treated by dissolving the polyisocyanate compound in an alcohol solution; S2: Under anhydrous conditions, corn fiber and acetoacetic acid are mixed in proportion, and hydroxyl groups on the surface of the corn fiber are modified by acetoacetic acid to obtain modified corn fiber A; S3: Laccase was used to degrade the lignin and cellulose network structure in flax fiber and wormwood fiber to disperse the fiber bundles, succinic anhydride was used to esterify the wormwood fiber to improve the interfacial compatibility between the fiber and the polymer matrix, and the esterified wormwood fiber was immersed in a lithium silicate mixed solution for coating to improve the thermal stability of the plant fiber, thereby obtaining modified wormwood fiber A; S4: soaking the degraded flax fiber in an acetylation agent solution, adding a trace amount of Lewis acid as a catalyst, acetylation treatment of the flax fiber, enhancing the interfacial bonding force between the flax fiber and the polymer matrix, and obtaining acetylated flax fiber. After the acetylation treatment is completed, a weak base (such as sodium carbonate solution) is used to neutralize the residual acid to prevent further degradation of the fiber, and the acetylated flax fiber is washed with a large amount of water to remove unreacted acetylation agent, catalyst and by-products, and the washed acetylated flax fiber is dried at low temperature to prevent heat damage, thereby obtaining modified flax fiber A. S5: Using hot volatile gas of hexamethyldisiloxane as the gas medium, a low-temperature plasma treatment apparatus was used to post-treat the three treated natural plant fibers at normal pressure to obtain modified flax fiber B, modified corn fiber B, and modified wormwood fiber B, thereby improving the interface compatibility between the fiber and the polymer matrix and enhancing the performance of the composite material; S6: dissolving jasmine extract in a solvent, stirring the solvent sufficiently to ensure that the extract is completely dissolved, immersing polyester fiber in the solution containing jasmine extract, mechanically stirring the solution so that the jasmine extract is loaded on the polyester fiber, taking out the fiber and drying it at 35° C., and performing heat setting treatment on the dried fiber to enhance the persistence of the fragrance, thereby obtaining loaded polyester fiber A; S7: polylactic acid is dried at high temperature, and the dried polylactic acid, graphene fiber and carbodiimide are first added to a mixing device for plasticizing and blending for 3 hours, with the temperature set at 165°C and the speed set at 50r / min. After the initial blending, triacetic acid, modified flax fiber B, modified corn fiber B, modified wormwood fiber B and acetyl tributyl citrate are added, and plasticizing and blending are performed for 5 minutes. Then, the loaded polyester fiber A is added and plasticized and blended again for 20 minutes, with the temperature set at 160°C and the speed set at 50r / min. After plasticizing and melting evenly, sheets are produced, and after lamination, they are hot pressed on a flat vulcanizer while hot, and then cold pressed on a cold press to room temperature, and dried and formed to obtain standard specimens; S8: irradiating the standard sample with gamma rays to obtain the final product, i.e., bio-based composite polylactic acid fiber.

2. The method for preparing a bio-based composite polylactic acid fiber according to claim 1, characterized in that: In the step S1, the alkaline solvent used for pretreatment is NaOH solution; the concentration of the NaOH solution is 3-5%; and the pretreatment temperature is 30-58°C.

3. The method for preparing a bio-based composite polylactic acid fiber according to claim 2, characterized in that: In the step S1, the polyisocyanate compound is selected from one of polyphenyl polyisocyanate, cyanurate, toluene diisocyanate and diphenylmethane diisocyanate; the alcohol solution is selected from one of propanol, pentanol, dodecanol and dodecanol mercaptan.

4. The method for preparing a bio-based composite polylactic acid fiber according to claim 3, characterized in that: In the step S2, before the corn fiber is mixed with acetoacetic acid, one of anhydrous sodium sulfate and molecular sieve is used to remove moisture; the reaction temperature is the reflux temperature; and the feed mass ratio of corn fiber to acetoacetic acid is 1:1.5-2.

5. The method for preparing a bio-based composite polylactic acid fiber according to claim 4, characterized in that: In the step S3, the lithium silicate mixed solution is prepared by mixing lithium silicate powder with ethanol solution, and the lithium silicate powder accounts for 5-10% of the total mass of the solution.

6. The method for preparing a bio-based composite polylactic acid fiber according to claim 5, characterized in that: In the step S4, the acetylation reagent is selected from acetyl chloride and acetic anhydride; the reaction temperature is 40-80°C; and the low-temperature drying temperature is 0-10°C.

7. The method for preparing a bio-based composite polylactic acid fiber according to claim 6, characterized in that: In the step S6, the mass ratio of the polyester fiber to the jasmine extract is 1:0.025-0.05; and the solvent is selected from one of ethanol and acetone.

8. The method for preparing a bio-based composite polylactic acid fiber according to claim 7, characterized in that: In the step S7, the components and addition amounts of the main raw materials are: 60 parts of polylactic acid, 3 to 7 parts of graphene fiber, 12 to 18 parts of modified flax fiber B, 4 to 10 parts of modified corn fiber B, 2 to 4 parts of modified wormwood fiber B, and 8 to 12 parts of loaded polyester fiber A.

9. The method for preparing a bio-based composite polylactic acid fiber according to claim 8, characterized in that: In the step S7, the amount of carbodiimide as an antioxidant is 1 to 3% of the amount of the main raw material; the amount of acetyl tributyl citrate is 0.5 to 1.1% of the amount of the main raw material.

10. The method for preparing a bio-based composite polylactic acid fiber according to claim 9, characterized in that: In the step S8, the radiation sensitizer is triallyl isocyanuric acid, and the amount of the radiation sensitizer added is 2%; the radiation dose is 30 kGy.

Citation Information

Patent Citations

  • Adjusting method of natural vegetable fiber and polylactic acid interface

    CN102241827A

  • Continuous fiber reinforced polylactic resin composition and preparation method thereof

    CN103665800A

  • Method for heterogeneously preparing acetoacetate cellulose material

    CN108641003A

  • Method for preparing floral fiber carpet and floral fiber carpet

    CN108914383A

  • Processing method of plant fiber

    CN109972403A